Survival after nephroureterectomy for upper tract urothelial carcinoma: A population‐based competing‐risks analysis. (29th August 2013) - Gandaglia, Giorgio; Bianchi, Marco; Trinh, Quoc‐Dien; Becker, Andreas; Larouche, Alexandre; Abdollah, Firas; Roghmann, Florian; Tian, Zhe; Shariat, Shahrokh F; Briganti, Alberto; Montorsi, Francesco; Karakiewicz, Pierre I; et al.
<x xml:space="preserve">Abstract</x> Objectives To examine the rates of cancer‐specific mortality, other‐cause and bladder cancer mortality in patients with upper‐tract urothelial carcinoma undergoing radical nephroureterectomy. Methods Relying on the Surveillance, Epidemiology, and End Results database, 9899 patients treated with radical nephroureterectomy were identified. A 20‐strata graphical aid was constructed using age (<60, 60–69, 70–79, >79 years) and American Joint Committee on Cancer/TNM stage (pT1N0/x, pT2N0/x, pT3N0/x, pT4N0/x, pTanypN1–3) as stratifying variables. The 5‐year cancer‐specific mortality, other‐cause and bladder cancer mortality rates were generated through competing‐risks Poisson regression methodologies. Multivariable competing‐risks regression models were used to test the effect of age and stage on three different end‐points: cancer‐specific mortality, other‐cause and bladder cancer mortality. Results Overall, 1797 (18.1%), 891 (9.1%) and 3090 (31.2%) patients died of cancer‐specific mortality, other‐cause and bladder cancer mortality, respectively. Following stratification according to age and stage, the proportion of patients who succumbed to cancer‐specific mortality (11.7–21.9%) and other‐cause mortality (8.9–30.4%) increased with age. In contrast, with increasing stage, the proportion of patients who died of cancer‐specific mortality increased (7.2–37.5%), whereas the proportion of other‐cause mortality remained stable (18.9–22.0%). The rate of bladder cancer mortality increased with advancing stage. At multivariable competing‐risk regression model, besides age and stage, women, type of surgery, grade and location were associated with higher cancer‐specific mortality. Furthermore, ureteral location, stage and grade were associated with bladder cancer mortality. Conclusions The developed graphical aid for prediction of cancer‐specific mortality, other‐cause, and bladder cancer mortality according to age and stage in patients with upper‐tract urothelial carcinoma undergoing radical nephroureterectomy can be useful for physicians and patients during clinical counseling.